The Association Between Cognitive Deficits and Clinical Characteristic in First-Episode Drug Naïve Patients With Schizophrenia - Peng, Xing-Jie; Hei, Gang-Rui; Yang, Ye; Liu, Chen-Chen; Xiao, Jing-Mei; Long, Yu-Jun; Huang, Jing; Zhao, Jing-Ping; Wu, Ren-Rong (Frontiers in Psychiatry, 2021)
Background: Schizophrenia is a severe mental disease which characterized by positive symptom, negative symptom, general pathology syndrome and cognitive deficits. In Recent years, many studies have investigated the relationship between cognitive deficits and clinical characteristics in schizophrenia, but relatively few studies were performed on first-episode drug-naïve patients. Methods: 87 first-episode drug-naïve schizophrenia patients were assessed for positive symptom, negative symptom, general pathology symptom and cognitive deficits from the Positive and Negative Symptom Scale and MATRICS Consensus Cognitive Battery. Psychotics depression were assessed using the Calgary depressing scale for schizophrenia. The relationship between clinical characteristics and cognitive deficits were assessed using correlation analysis and linear regression analysis. Results: The prevalence of cognitive deficits among the patients in our study was 85.1% (74/87) which was much higher than that in the general population. According to correlation analysis, negative symptom was negatively correlated with cognitive function, and general pathology showed a negative correlation with attention/vigilance. In addition, a positive correlation was found between age and speed of processing. No correlation was found between cognitive deficits and positive symptom. Conclusions: These results suggested: First, first-episode drug-naïve schizophrenia patients had severe cognitive impairment. Second, the negative symptom and the general symptomatology was negatively correlated with some domains of cognitive function, but no association were observed between positive symptom and cognitive impairment. Third, the age was positively correlated with the speed of processing, suggesting that patients may have better speed of processing with late onset of disease.